THE EFFECT OF PRODUCTION COSTS, LAND AREA, AND SELLING PRICES ON THE INCOME OF COPRA FARMERS (CASE STUDY OF FARMERS AT PT. ARGANTARA JAYA INDONESIA) - Soebekti, Buyung Kusuma; Kaihatu, Thomas Stefanus (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
The purpose of this study is to analyze the effect of production costs, land area, selling prices on the income of copra farmers who collaborate with PT. Argantara Jaya Indonesia. Copra farmers who collaborate with PT. Argantara Jaya Indonesia are located in the provinces of Lampung, East Nusa Tenggara, Maluku, North Maluku. The sample used in this study was 84 smoked copra farmers. The data analysis technique in this study used quantitative with multiple linear regression analysis methods. The results of the study showed that partially production costs had a significant negative effect on the income of copra farmers, partially land area had a significant positive effect on farmer income, partially selling prices had a significant negative effect on farmer income. Implementation PT Argantara Jaya Indonesia can focus on training that introduces more efficient copra production techniques and the use of modern tools to improve yields and product quality.